MEMBANGUN PEMBELAJARAN DEMOKRATIS BERWAWASAN MULTIKULTURAL - Fitriyah, Nur Laili (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
Negative phenomena which are found in this country, especially among students because of errors on the meaning of democracy must be followed up in order to be able to attain the education and return to the goal of producing bright young generation, democratic and not to ignore the environment around them and the diversity in culture and their beliefs. In order to achieve this, we a democratic learning by educators who have knowledge and awareness of freedom in proportionally meaning, awareness of diversity and multicultural in life and of course ability to implement them in learning.